Praktik Pernikahan dalam Masyarakat Lokal: Agensi versus Agama - Budiman Pohan; Muhamad Fadhil Nurdin (JSW (Jurnal Sosiologi Walisongo), 2020)
This study aims to describe the dialectical process between local agents and religious structures in the practice of marriage in Padang Sidempuan. The research method is qualitative descriptive with a case study design that focuses on narrating the objective conditions of agent and structure duality. Informants were chosen purposively, supported by observational data, interviews, and documentation. Data analyzed through the process of collection, reduction, exposition, verification, and conclusion. The results showed that: 1) Conceptually, the practice of marriage experienced practical distortions that were configured through consensus of sharia and local elites; 2) the practice of marriage is a phenomenon of the duality of agents and structuring each other; 3) agent habitus is dominated by Mandailing culture through power relations and surplus capital of the local elite compared to the sharia procedure of religious structure. However, the competence of agents is able to compress marital rules into semi-complex; 4) the importance of promoting religious habituation strategies through internalization and dissemination of alternative sharia marriage practices.